Histone Modifications, Internucleosome Dynamics, and DNA Stresses: How They Cooperate to “Functionalize” Nucleosomes - Krajewski, Wladyslaw A. (Frontiers in Genetics, 2022)
Tight packaging of DNA in chromatin severely constrains DNA accessibility and dynamics. In contrast, nucleosomes in active chromatin state are highly flexible, can exchange their histones, and are virtually ‘transparent’ to RNA polymerases, which transcribe through gene bodies at rates comparable to that on naked DNA. Defining mechanisms that revert nucleosome repression, besides their value for basic science, is of key importance for the diagnosis and treatment of genetic diseases. Chromatin activ-ity is largely regulated by histone post-translational modifications, ranging from small chemical groups up to the yet understudied “bulky” ubiquitylation and sumoylation. However, it is still to be revealed how histone marks are “translated” to permissive or repressive changes in nucleosomes: it is a general opin-ion that histone modifications act primarily as ‘signals’ for recruiting the regulatory proteins or as a ‘neu-tralizer’ of electrostatic shielding of histone tails. Here we would like to discuss recent evidence suggest-ing that histone ubiquitylation, in a DNA stress-dependent manner, can directly regulate dynamics of nu-cleosome and their primary structure, and can promote nucleosome decomposition to hexasome parti-cles or additionally stabilize nucleosomes against unwrapping. In addition, nucleosome repression/ de-repression studies are usually performed with single mononucleosomes as a model. We would like to review and discuss recent findings showing that internucleosome interactions could strongly modulate dynamics and rearrangements of nucleosomes. Our hypothesis is that bulky histone modifications, nu-cleosome inherent dynamics, internucleosome interactions and DNA torsions could act in cooperation to orchestrate formation of different dynamic states of arrayed nucleosomes, and thus promote chromatin functionality and diversify epigenetic programming methods.